MOULD RESISTANCE OF THE BAMBOO Thyrsostachys siamensis TREATED WITH OLEORESIN HEAT - Thi Kim Hong, Tang; Hien Mai, Trinh; Thi Thanh Hien, Nguyen (Journal of Forestry Science and Technology, 2022)
The bamboo Thyrsostachys siamensis is one of the most common species growing mainly and also largely cultivated in South Vietnam. The culms are the main raw material of many bamboo companies for industrial manufacturing of round and laminated bamboo furniture for exportation. Bamboo has low natural durability against fungi and insects. Compared with wood, bamboo is easier to damage by fungi and insects. An effective and eco-friendly method is needed to improve their physical and chemical properties, and mould resistance. In this research, mould resistance of the bamboo species Thyrostachys siamensis treated oleoresin heat under different temperatures (120ºC to 140ºC) and durations (60 min to 120 min) was tested in laboratory and field condition. Oleoresin used in this study is extracted from Dipterocarpus alatus. In the laboratory experiment, mould growth on the specimens was evaluated 1, 2, 4 and 8 weeks after they were exposed to the inoculation with a conidia mixture of six moulds isolated from infected bamboos. In the field experiment, evaluation of mould growth on the samples was done 1, 2, 4 and 8 weeks after exposure at the storage site of Bamboo factory, Binh Duong. The results showed that oleoresin heat treatment with D. alatus oleoresin at equal to 140ºC for at least 60 min completely inhibited mould growth on the bamboo T. siamensis.